Oxygen radical functionalization of boron nitride nanosheets - MAY, PETER; COLEMAN, JONATHAN; MCGOVERN, IGNATIUS; GOUNKO, IOURI; SATTI, AMRO (My University, 2012)
The covalent chemical functionalization of exfoliated hexagonal boron-nitride nanosheets (BNNSs) is achieved by the solution phase oxygen radical functionalization of boron atoms in the h-BN lattice. This involves a two-step procedure to initially covalently graft alkoxy groups to boron atoms and the subsequent hydrolytic defunctionalisation of the groups to yield hydroxyl-functionalized BNNSs (OH-BNNSs). Characterization of the functionalized-BNNSs using HR-TEM, Raman, UV-Vis, FTIR, NMR, and TGA was performed to investigate both the structure of the BNNSs and the covalent functionalization methodology. OH-BNNSs were used to prepare polymer nanocomposites and their mechanical properties analyzed. The influence of the functional groups grafted to the surface of the BNNSs is investigated by demonstrating the impact on mechanical properties of both non-covalent and covalent bonding at the interface between the nanofiller and polymer matrices.
PUBLISHED
Keywords: TS and JC would like to thank the European Research Council for funding through the grant; TS and JC would like to thank the European Research Council for funding through the grant; Nanoscience & Materials